How to prove that:

`sin^2xcos^3x=(sin^2x-sin^4x)cosx`

### 2 Answers | Add Yours

`sin^2xcos^3x=sin^2x(1-sin^2x)cosx=(sin^2x-sin^4x)cosx`

The identity `sin^2xcos^3x=(sin^2x-sin^4x)cosx` has to be proved.

Start with the left hand side

`sin^2xcos^3x`

= `sin^2x*cos^2x*cos x`

= `sin^2x*(1 - sin^2x)*cosx`

= `(sin^2x - sin^4x)*cos x`

**This proves that **`sin^2xcos^3x=(sin^2x-sin^4x)cosx`

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes